1995
DOI: 10.1002/1097-0142(19950915)76:6<985::aid-cncr2820760611>3.0.co;2-g
|View full text |Cite
|
Sign up to set email alerts
|

Adult acute lymphoblastic leukemia at relapse. Cytogenetic, immunophenotypic, and molecular changes

Abstract: Background. There have been published reports on cytogenetic, immunophenotypic, and molecular changes at relapse in childhood acute lymphoblastic leukemia (ALL) including lineage switch and secondary leukemia. There are limited data, however, on the cytogenetic, immunophenotypic, and molecular parameters of adult ALL at relapse. Because, as in children, the cytogenetic and/or immunophenotypic changes observed in adult ALL at relapse may have prognostic significance, the authors investigated the significance of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0

Year Published

1999
1999
2010
2010

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(15 citation statements)
references
References 11 publications
1
14
0
Order By: Relevance
“…This is not unexpected considering that several previous studies, using conventional chromosome banding techniques, have shown increased numbers of structural chromosome abnormalities in ALL, including high hyperdiploid cases, at relapse. [22][23][24][25][26][27] Using SNP array analysis, Mullighan et al 12 also observed significantly higher frequencies of deletions in relapse samples. In this study, most RTK-RAS mutations were detected at relapse.…”
Section: Discussionmentioning
confidence: 99%
“…This is not unexpected considering that several previous studies, using conventional chromosome banding techniques, have shown increased numbers of structural chromosome abnormalities in ALL, including high hyperdiploid cases, at relapse. [22][23][24][25][26][27] Using SNP array analysis, Mullighan et al 12 also observed significantly higher frequencies of deletions in relapse samples. In this study, most RTK-RAS mutations were detected at relapse.…”
Section: Discussionmentioning
confidence: 99%
“…Clonal evolution is not the only cytogenetic observation at relapse; some cases show entirely different karyotypes, thereby raising the possibility of secondary leukemia (Raimondi SC, 1993). Chucrallah et al (1995) analyzed 32 relapsed adult ALL patients and found that nine (28%) had clonal evolution, 12 (37%) had a different karyotype, and 11 (34%) had an unchanged karyotype.…”
Section: Discussionmentioning
confidence: 99%
“…Two major pitfalls have the potential to reduce the value of flow-cytometry immunophenotypic detection of MRD: the absence of leukemia-specific antigens and the existence of phenotypic changes at relapse that could induce false-negative results [4][5][6][7][8][32][33][34][35]. However, immunophenotypic detection of MRD is possible in acute leukemia because the neoplastic cells frequently express aberrant or unusual phenotypes.…”
Section: Methodologic Approachesmentioning
confidence: 99%
“…In addition, such abnormal or infrequent antigenic patterns remain relatively stable during the course of the disease [22,36]. Although phenotypic changes have been shown to occur at high frequencies (20%-70%) in acute leukemia they are less freqent in ALL than in acute myeloid leukemia, and most of these changes involve individual antigens that are associated with maturation [32][33][34][35][36]. In our experience, changes affecting aberrant phenotypes were much less frequent, and at least one of the aberrations detected at diagnosis remained stable at relapse.…”
Section: Methodologic Approachesmentioning
confidence: 99%
See 1 more Smart Citation